Traumatized triad of complementopathy, endotheliopathy, and coagulopathy ˗ Impact on clinical outcomes in severe polytrauma patients - Yang, Zhangsheng; Le, Tuan D.; Simovic, Milomir O.; Liu, Bin; Fraker, Tamara L.; Cancio, Tomas S.; Cap, Andrew P.; Wade, Charles E.; DalleLucca, Jurandir J.; Li, Yansong (Frontiers in Immunology, 2022)
Complementopathy, endotheliopathy, and coagulopathy following traumatic injury are key pathophysiological mechanisms potentially associated with multiple-organ failure (MOF) and mortality. However, the heterogeneity in the responses of complementopathy, endotheliopathy and coagulopathy to trauma, the nature and extent of their interplay, and their relationship to clinical outcomes remain unclear. Fifty-four poly-trauma patients were enrolled and divided into three subgroups based on their ISS. Biomarkers in blood plasma reflecting complement activation, endothelial damage, and coagulopathy were measured starting from admission to the emergency department and at 3, 6, 12, 24, and 120 hours after admission. Comparative analyses showed that severely injured patients (ISS>24) were associated with longer days on mechanical ventilation, in intensive care unit and hospital stays, and a higher incidence of hyperglycemia, bacteremia, respiratory failure and pneumonia compared to mildly (ISS<16) or moderately (ISS=16-24) injured patients. In this trauma cohort, complement was activated early, primarily through the alternative complement pathway. As measured in blood plasma, severely injured patients had significantly higher levels of complement activation products (C3a, C5a, C5b-9, and Bb), endothelial damage markers (syndecan-1, sTM, sVEGFr1, and hcDNA), and fibrinolytic markers (D-dimer and LY30) compared to less severely injured patients. Severely injured patients also had significantly lower thrombin generation (ETP and peak) and lower levels of coagulation factors (I, V, VIII, IX, protein C) compared to less severely injured patients. Complement activation correlated with endothelial damage and hypocoagulopathy. Logistic regression analyses revealed that Bb >1.57 μg/ml, syndecan-1 >66.6 ng/ml or D-dimer >6 mg/L at admission were associated with a higher risk of MOF/mortality. After adjusting for ISS, each increase of the triadic score defined above (Bb>1.57 µg/ml/Syndecan-1>66.6 ng/ml/D-dimer>6.0mg/L) was associated with a 6-fold higher in the odds ratio of MOF/death [OR: 6.83 (1.04-44.96, P=0.046], and a 4-fold greater in the odds of infectious complications [OR: 4.12 (1.04-16.36), P=0.044]. These findings provide preliminary evidence of two human injury response endotypes (traumatized triad and non-traumatized triad) that align with clinical trajectory, suggesting a potential endotype as defined by a high triadic score. Patients with this endotype may be considered for timely intervention to create a pro-survival/organ-protective phenotype and improve clinical outcomes.